Temperature sensitivity of soil carbon dioxide and nitrous oxide emissions in mountain forest and meadow ecosystems in China. (October 2016) - Zhang, Junjun; Peng, Changhui; Zhu, Qiuan; Xue, Wei; Shen, Yan; Yang, Yanzheng; Shi, Guohua; Shi, Shengwei; Wang, Meng
Abstract: An incubation experiment was conducted at three temperature levels (8, 18 and 28 °C) to quantify the response of soil CO2 and N2 O emissions to temperature in three ecosystems (pine forest, oak forest, and meadow) located in the Qinling Mountains of China, which are considered to be susceptible to disturbance and climate changes, especially global warming. The soil CO2 emission rates increased with temperature and decreased with soil depth; they were the highest in the oak forest (broadleaf forest) and were lower in the pine forest (coniferous forest) and the meadow ecosystem. However, there was no significant difference in the soil N2 O emission rates among the three ecosystems. The temperature sensitivity of CO2 and N2 O was higher in the forest than in the meadow ecosystem. The Q10 values (temperature sensitivity coefficient) for CO2 and N2 O were 1.07–2.25 and 0.82–1.22, respectively, for the three ecosystems. There was also evidence that the CO2 and N2 O emission rates were positively correlated. The soil characteristics exhibited different effects on CO2 and N2 O emissions among different ecosystems at the three temperature levels. Moreover, the soil dissolved organic carbon (DOC), specific ultraviolet absorbance (SUVA) and nitrate (NO3 − ) were important factors for CO2 emissions, whereas the soil ammonium (NH4 + ) and pH were the major controllers of N2 O emissions. Unexpectedly, our results indicated that CO2 emissions are more sensitive to increasing temperature than N2 O, noting the different feedback of CO2 and N2 O emissions to global warming in this region. The different responses of greenhouse gas emissions in different forest types and a meadow ecosystem suggest that it is critical to conduct a comprehensive investigation of the complex mountain forest and meadow ecosystem in the transitional climate zone under global warming. Our research results provide new insight and advanced understanding of the variations in major greenhouse gas emissions (CO2 and N2 O) and soil characteristics in response to warming. Highlights: CO2 emissions were higher in forests than meadow and greater in broadleaf forest. N2 O emissions showed small variation under different temperatures. A positive correlation was found between CO2 and N2 O emission rates. Q10 values for CO2 increased with temperature but changed slightly for N2 O.